Overvejelse om positioneret deltager-observation - sexede astronomer og kønnede læreprocesser - Hasse, Cathrine (Kvinder, Køn & Forskning, 2000)
The author give empirical examples from her fieldwork among physicist students in Copenhagen and discuss participant observation within a new methodological framework stressing that observation and participation is always positioned. Participant-observation is a generel method useful for men and alike. Even so the question raised by the author is whether this method leads to different genderdetermined research epistemologies as male and female scientists in some ways occupy two different positions in a particular social world, which leads to differences in evaluations and reactions and thereby to different epistemological processes and analyses of the object under study.